Diagnosis of Systemic Fungal Diseases - Dufresne, Simon Frédéric; Marr, Kieren A.; Shoham, Shmuel (Principles and Practice of Transplant Infectious Diseases, 2019)
Invasive fungal infections (IFI) are a major cause of morbidity and mortality in transplant recipients. The most common IFI are candidiasis, aspergillosis, pneumocystosis, cryptococcosis, mucormycosis, and endemic mycoses. Clinical presentations are generally non-specific, and fungal etiologies are often suspected when immunocompromised patients present with respiratory symptoms and/or undifferentiated fever that do not respond to empiric antibacterial therapy. Moreover, early treatment can be lifesaving. Consequently, diagnosis is a cornerstone for management of such patients, and rapid, accurate, and safe diagnostic techniques are critically important. Multiple diagnostic tools are available to clinicians. In addition to microscopy and culture, serodiagnosis and nucleic acid amplification techniques are emerging. Traditional and nontraditional methods are complementary, and judicious selection of tests in a given clinical setting is essential. This chapter reviews the diagnostic methods used in medical mycology and provides guidance to clinicians and laboratorians dealing with IFI in the transplant population.
Keywords: Antigen; Aspergillosis; Beta-D-glucan; Candidiasis; Culture; Diagnosis; Endemic mycoses; Galactomannan; Invasive fungal infections; Nucleic acid amplification technique

Defining Galactomannan Positivity in the Updated EORTC/MSGERC Consensus Definitions of Invasive Fungal Diseases - Mercier, Toine; Castagnola, Elio; Marr, Kieren A; Wheat, L Joseph; Verweij, Paul E; Maertens, Johan A (Clinical Infectious Diseases, 2021)
The consensus definitions of invasive fungal diseases from the EORTC/MSGERC were recently revised and updated. They now include consensus cutoff values for the galactomannan test that support the diagnosis of probable invasive aspergillosis. In this supplement article, we provide a rationale for these proposed thresholds based on the test’s characteristics and performance in different patient populations and in different specimen types.

Administration of voriconazole in patients with renal dysfunction - Neofytos, Dionissios; Lombardi, Lindsey R.; Shields, Ryan K.; Ostrander, Darin; Warren, Lindsay; Nguyen, M. Hong; Thompson, Carol B.; Marr, Kieren A. (Clinical Infectious Diseases: An Official Publication of the Infectious Diseases Society of America, 2012)
BACKGROUND: The intravenous use of voriconazole requires coadministration with sulphobutylether-β-cyclodextrin, which may accumulate in patients with impaired renal function. METHODS: All adult patients treated with the same formulation of voriconazole for a minimum of 3 consecutive days were included. Renal function was assessed based on the creatinine level and the calculated creatinine clearance (CrCl). Change in renal function was calculated on days 3, 7, and end of treatment (EOT) and was defined based on the RIFLE criteria. RESULTS: Among 166 patients in whom baseline renal function was assessed, 42 (25.3%) had a CrCl <50 mL/min and received intravenous voriconazole, 77 (46.4%) had a CrCl ≥50 mL/min and received intravenous voriconazole, and 47 (28.3%) had a CrCl <50 mL/min and were treated with oral voriconazole. Renal function changed on days 3, 7, and EOT in 19 (11.4%), 14 (8.4%), and 28 (16.9%) patients, respectively. Multivariate analyses identified significant predictors of renal dysfunction: (1) day 3, hematologic malignancy (odds ratio [OR], 5.09, P = .01), fluconazole use within 30 days prior to voriconazole (OR, 6.21; P = .008), coadministration of penicillins (OR, 6.12; P = .03), and immunosuppressants (OR, 7.00; P = .002); (2) day 7, baseline liver impairment (OR, 5.30; P value = .004); (3) EOT, administration of penicillins (OR, 2.39; P = .04). CONCLUSIONS: Voriconazole route of administration and baseline renal function were not predictors of worsening renal dysfunction on days 3, 7, and EOT. Underlying disease, baseline liver impairment, and concomitant administration of other drugs (eg, penicillins, fluoroquinolones, immunosuppressants) were the strongest predictors of renal dysfunction.
Keywords: Adult; Aged; Aged; 80 and over; Antifungal Agents; Creatinine; Female; Humans; Infusions; Intravenous; Kidney Diseases; Male; Metabolic Clearance Rate; Middle Aged; Mycoses; Pyrimidines; Renal Insufficiency; Retrospective Studies; Triazoles; Voriconazole; Young Adult

Development of an Interferon-Gamma Release Assay (IGRA) to Aid Diagnosis of Histoplasmosis - Datta, Kausik; LaRue, Richard; Permpalung, Nitipong; Das, Sukanya; Zhang, Sean; Mehta Steinke, Seema; Bushkin, Yuri; Nosanchuk, Joshua D.; Marr, Kieren A. (Journal of Clinical Microbiology)
Establishing diagnosis of latent and active histoplasmosis is challenging. Interferon gamma-release assays (IGRAs) may provide evidence of latent and active infection. An enzyme-linked immunospot (ELISpot) assay was developed using yeast cell lysate (YCL) antigen prepared from a representative North American Histoplasma capsulatum strain. Assay parameters were optimized by measuring responses in healthy volunteers with and without Histoplasma infection. Assay performance as an aid for diagnosing histoplasmosis was assessed in a prospective cohort of 88 people with suspected or confirmed infection, and 44 healthy controls enrolled in two centers in North America (2013 to 2018). Antigen specificity of IFN-γ release was demonstrated using ELISpot and enzyme-linked immunosorbent assay (ELISA). Antigen-evoked, single-cell mRNA expression by memory T cells was shown using flow cytometry. The area under the receiver operating characteristic curve (AUC) was estimated at 0.89 (95% confidence interval [CI]: 78.5% to 99.9%). At optimal cutoff, sensitivity was 77.2% (95% CI: 54.6% to 92.2%) and specificity was 100% (95% CI: 89.7% to 100%). Sixteen of 44 healthy volunteers (36.4%) from a region of hyperendemicity had positive responses, suggesting detection of previously unrecognized (latent) infection. The ELISpot assay is sensitive and specific as an aid to diagnose H. capsulatum infection and disease, supporting proof of concept and further development.

Invasive fungal infections after respiratory viral infections in lung transplant recipients are associated with lung allograft failure and chronic lung allograft dysfunction within 1 year - Permpalung, Nitipong; Liang, Tao; Gopinath, Shilpa; Bazemore, Katrina; Mathew, Joby; Ostrander, Darin; Durand, Christine M.; Shoham, Shmuel; Zhang, Sean X.; Marr, Kieren A.; Avery, Robin K.; Shah, Pali D. (The Journal of Heart and Lung Transplantation, 2023)

Clinical Practice Guideline for the Management of Candidiasis: 2016 Update by the Infectious Diseases Society of America - Pappas, Peter G.; Kauffman, Carol A.; Andes, David R.; Clancy, Cornelius J.; Marr, Kieren A.; Ostrosky-Zeichner, Luis; Reboli, Annette C.; Schuster, Mindy G.; Vazquez, Jose A.; Walsh, Thomas J.; Zaoutis, Theoklis E.; Sobel, Jack D. (Clinical Infectious Diseases, 2016)
Abstract. It is important to realize that guidelines cannot always account for individual variation among patients. They are not intended to supplant physician

Invasive Fungal Infections in Inpatient Solid Organ Transplant Recipients With COVID-19: A Multicenter Retrospective Cohort - Permpalung, Nitipong; Chiang, Teresa Po-Yu; Manothummetha, Kasama; Ostrander, Darin; Datta, Kausik; Segev, Dorry L.; Durand, Christine M.; Mostafa, Heba H.; Zhang, Sean X.; Massie, Allan B.; Marr, Kieren A.; Avery, Robin K. (Transplantation)
Background. The prevalence and outcomes of COVID-19-associated invasive fungal infections (CAIFIs) in solid organ transplant recipients (SOTRs) remain poorly understood. Methods. A retrospective cohort study of SOTRs with COVID-19 admitted to 5 hospitals within Johns Hopkins Medicine was performed between March 2020 and March 2022. Cox regression multilevel mixed-effects ordinal logistic regression was used. Results. In the cohort of 276 SOTRs, 22 (8%) developed IFIs. The prevalence of CAIFIs was highest in lung transplant recipients (20%), followed by recipients of heart (2/28; 7.1%), liver (3/46; 6.5%), and kidney (7/149; 4.7%) transplants. In the overall cohort, only 42 of 276 SOTRs (15.2%) required mechanical ventilation; these included 11 of 22 SOTRs (50%) of the CAIFI group and 31 of 254 SOTRs (12.2%) of the no-CAIFI group. Compared with those without IFIs, SOTs with IFIs had worse outcomes and required more advanced life support (high-flow oxygen, vasopressor, and dialysis). SOTRs with CAIFIs had higher 1-y death-censored allograft failure (hazard ratio 1.65.116.4, P = 0.006) and 1-y mortality adjusting for oxygen requirement (adjusted hazard ratio 1.12.45.1, P < 0.001), compared with SOTRs without CAIFIs. Conclusions. The prevalence of CAIFIs in inpatient SOTRs with COVID-19 is substantial. Clinicians should be alert to the possibility of CAIFIs in SOTRs with COVID-19, particularly those requiring supplemental oxygen, regardless of their intubation status.

Treatment of Aspergillosis: Clinical Practice Guidelines of the Infectious Diseases Society of America - Walsh, Thomas J.; Anaissie, Elias J.; Denning, David W.; Herbrecht, Raoul; Kontoyiannis, Dimitrios P.; Marr, Kieren A.; Morrison, Vicki A.; Segal, Brahm H; Steinbach, William J.; Stevens, David A.; Burik, Jo‐Anne van; Wingard, John R.; et al. (Clinical Infectious Diseases, 2008)

Practice Guidelines for the Diagnosis and Management of Aspergillosis: 2016 Update by the Infectious Diseases Society of America - Patterson, Thomas F.; Thompson, III, George R.; Denning, David W.; Fishman, Jay A.; Hadley, Susan; Herbrecht, Raoul; Kontoyiannis, Dimitrios P.; Marr, Kieren A.; Morrison, Vicki A.; Nguyen, M. Hong; Segal, Brahm H.; Steinbach, William J.; et al. (Clinical Infectious Diseases, 2016)
It is important to realize that guidelines cannot always account for individual variation among patients. They are not intended to supplant physician judgment with respect to particular patients or special clinical situations. IDSA considers adherence to these guidelines to be voluntary, with the ultimate determination regarding their application to be made by the physician in the light of each patient's individual circumstances.

Combination antifungal therapy for invasive aspergillosis: a randomized trial - Marr, Kieren A.; Schlamm, Haran T.; Herbrecht, Raoul; Rottinghaus, Scott T.; Bow, Eric J.; Cornely, Oliver A.; Heinz, Werner J.; Jagannatha, Shyla; Koh, Liang Piu; Kontoyiannis, Dimitrios P.; Lee, Dong-Gun; Nucci, Marcio; et al. (Annals of Internal Medicine, 2015)
BACKGROUND: Invasive aspergillosis (IA) is associated with poor outcomes in patients with hematologic malignancies (HMs) and hematopoietic cell transplantation (HCT). Small studies suggest a role for combination antifungal therapy. OBJECTIVE: To assess the safety and efficacy of voriconazole and anidulafungin compared with voriconazole monotherapy for treatment of IA. DESIGN: Randomized, double-blind, placebo-controlled multicenter trial. (ClinicalTrials.gov: NCT00531479). SETTING: 93 international sites. PATIENTS: 454 patients with HM or HCT and suspected or documented IA were randomly assigned to treatment with voriconazole and anidulafungin or placebo. Primary analysis was done in the modified intention-to-treat population of 277 patients in whom IA was confirmed. MEASUREMENTS: The primary outcome was 6-week mortality; secondary outcomes included 12-week mortality, mortality in major subgroups, and safety measures. RESULTS: Mortality rates at 6 weeks were 19.3% (26 of 135) for combination therapy and 27.5% (39 of 142) for monotherapy (difference, -8.2 percentage points [95% CI, -19.0 to 1.5]; P = 0.087). Secondary mortality outcomes favored combination therapy. Multivariable regression analysis suggested that maximum galactomannan value, Karnofsky score, and baseline platelet count had prognostic significance. Most patients (218 of 277 [78.7%]) had IA diagnosis established by radiographic findings and maximum galactomannan positivity. In a post hoc analysis of this dominant subgroup, 6-week mortality was lower in combination therapy than monotherapy (15.7% [17 of 108] vs. 27.3% [30 of 110]; difference, -11.5 percentage points [CI, -22.7 to -0.4]; P = 0.037). Safety measures, including hepatotoxicity, were not different. LIMITATIONS: Mortality at 6 weeks was higher than expected, and the difference in mortality was lower than expected, which reduced power to detect a treatment effect. Enrollment was restricted to patients with HM or HCT, which limited generalizability. CONCLUSION: Compared with voriconazole monotherapy, combination therapy with anidulafungin led to higher survival in subgroups of patients with IA. Limitations in power preclude definitive conclusions about superiority. PRIMARY FUNDING SOURCE: Pfizer.
Keywords: Adolescent; Adult; Aged; Aged; 80 and over; Antifungal Agents; Aspergillosis; Double-Blind Method; Drug Therapy; Combination; Echinocandins; Female; Hematologic Neoplasms; Hematopoietic Stem Cell Transplantation; Humans; Karnofsky Performance Status; Male; Mannans; Middle Aged; Platelet Count; Treatment Outcome; Voriconazole; Young Adult

Randomized, double-blind trial of fluconazole versus voriconazole for prevention of invasive fungal infection after allogeneic hematopoietic cell transplantation - Wingard, John R.; Carter, Shelly L.; Walsh, Thomas J.; Kurtzberg, Joanne; Small, Trudy N.; Baden, Lindsey R.; Gersten, Iris D.; Mendizabal, Adam M.; Leather, Helen L.; Confer, Dennis L.; Maziarz, Richard T.; Stadtmauer, Edward A.; et al. (Blood, 2010)
Invasive fungal infection (IFI) is a serious threat after allogeneic hematopoietic cell transplant (HCT). This multicenter, randomized, double-blind trial compared fluconazole (N = 295) versus voriconazole (N = 305) for the prevention of IFI in the context of a structured fungal screening program. Patients undergoing myeloablative allogeneic HCT were randomized before HCT to receive study drugs for 100 days, or for 180 days in higher-risk patients. Serum galactomannan was assayed twice weekly for 60 days, then at least weekly until day 100. Positive galactomannan or suggestive signs triggered mandatory evaluation for IFI. The primary endpoint was freedom from IFI or death (fungal-free survival; FFS) at 180 days. Despite trends to fewer IFIs (7.3% vs 11.2%; P = .12), Aspergillus infections (9 vs 17; P = .09), and less frequent empiric antifungal therapy (24.1% vs 30.2%, P = .11) with voriconazole, FFS rates (75% vs 78%; P = .49) at 180 days were similar with fluconazole and voriconazole, respectively. Relapse-free and overall survival and the incidence of severe adverse events were also similar. This study demonstrates that in the context of intensive monitoring and structured empiric antifungal therapy, 6-month FFS and overall survival did not differ in allogeneic HCT recipients given prophylactic fluconazole or voriconazole. This trial was registered at www.clinicaltrials.gov as NCT00075803.

Isavuconazole versus voriconazole for primary treatment of invasive mould disease caused by Aspergillus and other filamentous fungi (SECURE): a phase 3, randomised-controlled, non-inferiority trial - Maertens, Johan A.; Raad, Issam I.; Marr, Kieren A.; Patterson, Thomas F.; Kontoyiannis, Dimitrios P.; Cornely, Oliver A.; Bow, Eric J.; Rahav, Galia; Neofytos, Dionysios; Aoun, Mickael; Baddley, John W.; Giladi, Michael; et al. (The Lancet, 2016)
Summary Background Isavuconazole is a novel triazole with broad-spectrum antifungal activity. The SECURE trial assessed efficacy and safety of isavuconazole versus voriconazole in patients with invasive mould disease. Methods This was a phase 3, double-blind, global multicentre, comparative-group study. Patients with suspected invasive mould disease were randomised in a 1:1 ratio using an interactive voice–web response system, stratified by geographical region, allogeneic haemopoietic stem cell transplantation, and active malignant disease at baseline, to receive isavuconazonium sulfate 372 mg (prodrug; equivalent to 200 mg isavuconazole; intravenously three times a day on days 1 and 2, then either intravenously or orally once daily) or voriconazole (6 mg/kg intravenously twice daily on day 1, 4 mg/kg intravenously twice daily on day 2, then intravenously 4 mg/kg twice daily or orally 200 mg twice daily from day 3 onwards). We tested non-inferiority of the primary efficacy endpoint of all-cause mortality from first dose of study drug to day 42 in patients who received at least one dose of the study drug (intention-to-treat [ITT] population) using a 10% non-inferiority margin. Safety was assessed in patients who received the first dose of study drug. This study is registered with ClinicalTrials.gov, number NCT00412893. Findings 527 adult patients were randomly assigned (258 received study medication per group) between March 7, 2007, and March 28, 2013. All-cause mortality from first dose of study drug to day 42 for the ITT population was 19% with isavuconazole (48 patients) and 20% with voriconazole (52 patients), with an adjusted treatment difference of −1·0% (95% CI −7·8 to 5·7). Because the upper bound of the 95% CI (5·7%) did not exceed 10%, non-inferiority was shown. Most patients (247 [96%] receiving isavuconazole and 255 [98%] receiving voriconazole) had treatment-emergent adverse events (p=0·122); the most common were gastrointestinal disorders (174 [68%] vs 180 [69%]) and infections and infestations (152 [59%] vs 158 [61%]). Proportions of patients with treatment-emergent adverse events by system organ class were similar overall. However, isavuconazole-treated patients had a lower frequency of hepatobiliary disorders (23 [9%] vs 42 [16%]; p=0·016), eye disorders (39 [15%] vs 69 [27%]; p=0·002), and skin or subcutaneous tissue disorders (86 [33%] vs 110 [42%]; p=0·037). Drug-related adverse events were reported in 109 (42%) patients receiving isavuconazole and 155 (60%) receiving voriconazole (p<0·001). Interpretation Isavuconazole was non-inferior to voriconazole for the primary treatment of suspected invasive mould disease. Isavuconazole was well tolerated compared with voriconazole, with fewer study-drug-related adverse events. Our results support the use of isavuconazole for the primary treatment of patients with invasive mould disease. Funding Astellas Pharma Global Development, Basilea Pharmaceutica International.

Revision and Update of the Consensus Definitions of Invasive Fungal Disease From the European Organization for Research and Treatment of Cancer and the Mycoses Study Group Education and Research Consortium - Donnelly, J Peter; Chen, Sharon C; Kauffman, Carol A; Steinbach, William J; Baddley, John W; Verweij, Paul E; Clancy, Cornelius J; Wingard, John R; Lockhart, Shawn R; Groll, Andreas H; Sorrell, Tania C; Bassetti, Matteo; et al. (Clinical Infectious Diseases, 2020)
Invasive fungal diseases (IFDs) remain important causes of morbidity and mortality. The consensus definitions of the Infectious Diseases Group of the European Organization for Research and Treatment of Cancer and the Mycoses Study Group have been of immense value to researchers who conduct clinical trials of antifungals, assess diagnostic tests, and undertake epidemiologic studies. However, their utility has not extended beyond patients with cancer or recipients of stem cell or solid organ transplants. With newer diagnostic techniques available, it was clear that an update of these definitions was essential.To achieve this, 10 working groups looked closely at imaging, laboratory diagnosis, and special populations at risk of IFD. A final version of the manuscript was agreed upon after the groups’ findings were presented at a scientific symposium and after a 3-month period for public comment. There were several rounds of discussion before a final version of the manuscript was approved.There is no change in the classifications of “proven,” “probable,” and “possible” IFD, although the definition of “probable” has been expanded and the scope of the category “possible” has been diminished. The category of proven IFD can apply to any patient, regardless of whether the patient is immunocompromised. The probable and possible categories are proposed for immunocompromised patients only, except for endemic mycoses.These updated definitions of IFDs should prove applicable in clinical, diagnostic, and epidemiologic research of a broader range of patients at high-risk.